Elder Mistreatment Among Older Chinese Americans: The Role of Family Cohesion. (April 2019) - Gao, Xiang; Sun, Fei; Marsiglia, Flavio F.; Dong, Xinqi
Cultural values are believed to influence perceptions of and solutions to elder mistreatment (EM) perpetrated by family members. This study aimed to understand the influence of family cohesion on EM reported by community-dwelling older Chinese Americans. A mixed-method approach consisting of a quantitative survey built on focus group interviews was utilized. Focus group interviews were conducted to ensure subsequent survey questions about EM were culturally and linguistically appropriate. The revised survey questionnaires were then administered to 266 Chinese American older adults to assess estimated EM prevalence and the effects of family cohesion. Survey findings indicate that 1 in 10 reported at least one occurrence of EM in the past year. Depressed Chinese older adults (OR= 1.14) and those reporting low levels of family cohesion (OR = .82) were more likely to experience EM. Multigenerational family interventions can be designed to reduce older adults' depression levels and promote family cohesion.